Projection solutions of Frobenius-Perron operator equations - Jiu Ding; Tien Tien Li (International Journal of Mathematics and Mathematical Sciences)
We construct in this paper the first order and second order piecewise polynomial finite approximation schemes for the computation of invariant measures of a class of nonsingular measurable transformations on the unit interval of the real axis. These schemes are based on the Galerkin's projection method for L1-spaces and are proved to be convergent for the class of Frobenius-Perron operators.